Impact of adiponectin and oxidized low-density lipoprotein in acute coronary syndrome - Batool Luay Aziz; Ahmed Hussein Al-Mayali; Shaymaa Zahraw Nada; Fatemah Abdullah Mankhi (Journal of Contemporary Medical Sciences, 2017)
Objectives This study aimed to investigate and measure the relationships between the adiponectin levels and oxidized-low density lipoprotein (Ox-LDL) in acute coronary syndrome (ACS) patients in holy Kerbala city, Iraq. Methods Fifty-eight patients included in the study. Patients admitted with a diagnosis of ACS and 30 control subjects. Circulating adiponectin and Ox-LDL were assessed; using enzyme-linked immunosorbent assays (ELISA). Results Adiponectin serum concentrations were signifcantly lower (p < 0.001) in subjects with ACS compared with control subjects. Ox-LDL serum concentrations were signifcantly higher (p < 0.001) in subjects with ACS compared with controls subjects. The ACS patients showed a signifcantly higher (p < 0.001) result in total cholesterol and signifcantly lower (p < 0.001) level in HDL-C. Conclusion Serum adiponectin negatively correlated with Ox-LDL level in patient group ACS and the healthy control group.